Spinal anesthesia with caudal catheter in pediatric urologic surgery: an alternative to general anesthesia - Stangl-Kremser, Judith; Puttmann, Kathleen; Alpert, Seth A.; Ching, Christina; DaJusta, Daniel; Fuchs, Molly; McLeod, Daryl; Jayanthi, Venkata R.; Ebert, Kristin (Frontiers in Pediatrics, 2025)
IntroductionTo evaluate feasibility and outcomes of children undergoing complex urologic surgery who received spinal-caudal catheter (SCC) anesthesia compared to those who received general anesthesia (GA).MethodsA retrospective single-center analysis of children scheduled for urologic surgery under SCC anesthesia between 2016 and 2019 was performed. This group was compared with an age- and urologic procedure-paired GA cohort that included cases since 2010. Outcomes of interest included induction and operative times, intraoperative medication use, as well as anesthesia complications.ResultsEach cohort was comprised of 52 patients. Induction times were longer with a mean difference of 4 min (p = 0.009) whilst operative times were shorter for the SCC group with a mean difference 34 min (p < 0.001). Mean intraoperative opioid dose was lower in the SCC group (0.014 vs. 0.19 MED/kg, p < 0.001). Fewer patients in the SCC group received corticosteroids (3.8% vs. 78.8%, p < 0.001). Complication rates did not differ significantly. There were two anesthesia related complications in the SCC group: transient myoclonic movement and retained catheter fragment; one GA case had intraoperative laryngospasm.ConclusionSCC anesthesia is feasible in most patients undergoing complex urologic surgery as an alternative to GA. Although induction times are slightly longer, this may be worth the benefit, as regional anesthesia may reduce the need for using an airway device and intraoperative opioid use.